Heat transfer and friction factor correlation development for double-pass solar air heater having V-shaped ribs as roughness elements. Issue 1 (2nd January 2017) - Sharma, A.; Bharadwaj, G.; Varun,
Abstract : In this present study, an experimental investigation has been carried out for a roughened double-pass solar air heater. The respective variation in other parameters, such as relative roughness pitch ( p / e ), relative roughness height ( e / D h ), and angle of attack (α), were 5–20, 0.022–0.044, and 30°–75°, respectively. The effect of roughness and operating parameters on Nusselt number (Nu) and friction factor ( f ) has been determined, and the results are compared with those of a smooth absorber plate; considerable enhancement in both heat transfer and friction factor is noticed. Utilizing these experimental data, correlations for Nusselt number and friction factor correlations were also developed.